The Experimental Evaluation of Cone Wedge Shape based Electronic Wedge Brake Mechanism in Vehicle Braking System - Sharil Izwan Haris; Fauzi Ahmad; Mohd Hanif Che Hassan; Ahmad Kamal Mat Yamin (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2022)
The brake system is one of the most critical parts of a vehicle's technology for avoiding accidents. The ultimate focus of the braking system is to guarantee that adequate stopping force is available to stop the vehicle's longitudinal movement. Therefore, the ability of a brake system to stop a vehicle must be examined in terms of analyzing the brake system's performance and the implementation of the brake system on actual vehicles. This study offers a performance evaluation of the Electronic Wedge Brake based on the Cone Wedge Shape (CW-EWB) on the vehicle brake systems. The evaluation was carried out through dynamic assessments, namely sudden braking tests at constant speeds of 40, 60, and 90 km/h using the MATLAB Simulink software simulation method and an experimental study using hardware-in-loop simulation (HILS). In the simulation study, the performance of the vehicle brake system using CW-EWB was compared with the brake performance of the vehicle using the conventional hydraulic brake (CHB). The results showed that CW-EWB behaved similarly to the hydraulic brake in terms of required brake torque output but with a faster response time, i.e., between 0.5 – 1 s. The HILS experimental study was conducted to evaluate the performance of the CW-EWB on actual vehicles. This method confirmed the HILS results against the simulation results with a variable response time of less than 6%. Vehicle body speed, wheel speed, longitudinal tire slip, and stopping distance experienced by the vehicle were all evaluated. The study's findings show that the proposed CW-EWB is quite effective and sufficiently dependable to be used as a vehicle brake system, notably in Antilock Braking Systems.